Using Genetic Technologies To Reduce, Rather Than Widen, Health Disparities - Smith, Caren E; Fullerton, Stephanie M; Dookeran, Keith A; Hampel, Heather; Tin, Adrienne; Maruthur, Nisa M; Schisler, Jonathan C; Henderson, Jeffrey A; Tucker, Katherine L; Ordovás, José M (Health affairs (Millwood, Va.), 2016)
Evidence shows that both biological and nonbiological factors contribute to health disparities. Genetics, in particular, plays a part in how common diseases manifest themselves. Today, unprecedented advances in genetically based diagnoses and treatments provide opportunities for personalized medicine. However, disadvantaged groups may lack access to these advances, and treatments based on research on non-Hispanic whites might not be generalizable to members of minority groups. Unless genetic technologies become universally accessible, existing disparities could be widened. Addressing this issue will require integrated strategies, including expanding genetic research, improving genetic literacy, and enhancing access to genetic technologies among minority populations in a way that avoids harms such as stigmatization.